Polypoid multifocal ileo-colonic amyloidoma masquerading malignancy - A rare case report - Halder, Aniket; Ghosh, Ranajoy; Ray, Sukanta (Indian Journal of Case Reports, 2019)
Amyloidosis is a group of disorders characterized by extracellular deposition of a proteinaceous homogenous eosinophilic hyaline substance known as amyloid. Congo red staining is a specific stain for amyloid which shows an apple-green birefringence on polarized microscopy. Amyloid deposition can be systemic or localized. Primary amyloidosis (also known as AL amyloidosis) is the most common form of amyloidosis characterized by generalized deposition of excess immunoglobulin light chains. It is associated with an underlying plasma cell dyscrasia and has the maximum gastrointestinal (GI) involvement. Secondary amyloidosis is characterized by deposition of acute-phase reactant - serum amyloid A protein (also known as AA amyloidosis) and it is associated with infectious, inflammatory, or less commonly, neoplastic disorders. Renal dysfunction is the most common symptom of AA amyloidosis at diagnosis. Amyloidosis presenting as a localized mass is known as amyloidoma. Amyloidoma of the GI system is a rare finding in the absence of any systemic involvement. We report a rare case of localized multifocal polypoid amyloidoma in the lower GI tract, which masquerades as malignancy.